Uncovering the History of the Nazi Holocaust in Senegal Through Artistic and Historical Research - Turpin, Joe (Arts Research Africa, 2022)
This paper describes the author’s residency in Dakar, Senegal, where he created artworks in response to the history of anti-Semitic laws and the Sébikhotane concentration camp, established by the Vichy French Colonial Regime in West Africa. The artworks aim to inform audiences about this littleknown history and use symbolism that Senegalese people can relate to. The paper discusses the research conducted, the positive reception of the artworks, and the author’s role as an artist, researcher, and performer. The paper also provides descriptions and explanations of some of the artworks created during the residency.